PARENTING STRESS AMONG PARENTS: A COMPARATIVE STUDY OF CHILD TYPE, FAMILY TYPE, AND CHILD GENDER - Pandya, Dipendra Jayantilal; Shukla, Parulben (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study aims to explore the parenting stress levels among different groups of parents based on (a) whether they have normal or special children, (b) their family structure (joint vs nuclear families), and (c) the gender of the child (boy or girl). A sample of 300 parents was selected from North Gujarat using stratified random sampling. Parenting Stress Index–Short Form (PSI-SF) developed by Abidin (1995) was administered. Results indicated that parents of special children experienced significantly higher stress compared to parents of normal children. Parents living in nuclear families reported higher stress levels compared to those in joint families. No significant difference was found between parents of boys and girls.